Development of Arduino-based high heat detector temperature control prototype for household appliances - Casinillo, Rhoda Mae L.; So, Allecia Leona A.; Mandaya, Maezel V.; Dabalos, Sonny Adrian J.; Enriquez, Mark Ceasar S.; Cane, Jas Felicisimo (IAES International Journal of Robotics and Automation (IJRA), 2024)
In the Philippines, fires are a widespread concern, with plenty of incidents attributed to electrical appliances. These incidents are a leading cause of non-open flame fires in the country, highlighting the urgent need for preventative measures. Existing devices could only trigger an alarm at 100 °C without shutting off the appliance automatically. To address these limitations, the researchers aimed to develop a high heat detector with 95% detection accuracy and less than 5% error in detecting high heat. This device used an Arduino Uno Board and relay to trigger an automated power-off mechanism in appliances experiencing high heat. Temperature changes were detected, and alarms were activated using an LM35 temperature sensor and buzzer. The accuracy of the LM35 sensor was assessed through hot bath tests, which included 12 trials at each temperature level between 80 °C and 150 °C with 10 °C intervals. The prototype’s performance revealed an average error rate of 1.13% and an average standard deviation of 0.9403. The computed F1 Score of 98% indicated that the prototype fulfilled the objectives. Functionality tests confirmed that the prototype successfully achieved its intended goal by shutting off the appliance when the threshold temperature was reached and enabling its operation otherwise.